The Effect of Service Quality, Brand Image, and Customer Satisfaction on Customer Loyalty on the Traveloka Application - Reynaldo bimantaka; Muchsin Muthohar (Jurnal Economic Resource, 2023)
Customer loyalty is a form of positive relationship that comes from the quality of service and the brand image of the manufacturer to give rise to consumer satisfaction. This study aims to identify the effect of service quality, brand image, and customer satisfaction on customer loyalty at Traveloka. This study used a non-probability convenience sampling technique in sampling. Primary data collected in this study amounted to 250 respondents. The statistical analysis technique used in this study is Structural Equation Modelling (SEM) with SmartPLS version 3.2.9 software. The results of the data analysis show that service quality has a positive and significant influence on brand image, customer satisfaction, and customer loyalty. Brand image has a positive and significant influence on customer satisfaction and loyalty, as well as customer satisfaction which has a positive and significant influence on customer loyalty.